KEBIJAKAN PENDIDIKAN DASAR (WAJIB BELAJAR SEMBILAN TAHUN) - Alsri Nurcahya; Ahmad Qurtubi; Anis Fauzi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
The basic education policy, especially the 9-year compulsory education program, is a government effort to improve the accessibility and quality of education for the entire society. The effort to make it compulsory for children to complete a minimum education for nine years has the primary objective of providing equal opportunities for all children to obtain an adequate basic education, improving access to education, reducing school dropouts, and improving the quality of education. Implementation of this policy is expected to have a good impact on reducing school dropout rates and increasing education participation at the elementary level. However, there are many challenges in ensuring the sustainability of the program, such as adequate infrastructure, the availability of quality educational resources, and meeting the needs of students with diverse educational backgrounds. The method used in this research is library studies, which involves collecting literature, gathering relevant data or information, and studying topics or issues related to the development of the Basic Education Policy, Compulsory Learning 9 Years. Therefore, there is a need for efforts in the evaluation and adaptation of this policy in order to achieve the primary objective of equal and quality basic education.